Molecular dynamics simulations of the isotopic effect on nanoscale friction - Matté, Daniel (My University, 2021)
Computer simulations are becoming increasingly useful for studying friction, enabling the application of controlled conditions, uncoupling mechanisms, and set-ups that are not usually achievable in physical experiments, ensuring that no other undesirable variable is acting on the system. In this work, molecular dynamics (MD) simulations were used to systematically explore the isotope's mass effect on the phononic contribution to friction by simulating different load conditions, sliding direction, and surface coverage of H-passivated fat [111] single-crystal diamond surfaces. Simulations were performed using the Adaptive Intermolecular Reactive Empirical Bond-Order (AIREBO) potential, including van der Waals interactions. The coeffcient of friction was found to be independent of the adsorbate atomic mass for both sliding directions simulated. Furthermore, at least in the simulated conditions, a simple reduction in surface coverage also did not signifcantly affect the coefficient of friction. A marked increase of friction force was observed only when the passivation layer was modified by introducing highly reactive defects. Accordingly, the results from MD simulations give support to an indirect isotopic effect on friction, but only to the extent that defects created in the passivation layer lead to the formation of highly reactive surfaces. [resumo fornecido pelo autor]
As simulações computacionais estão se tornando cada vez mais úteis para o estudo do atrito, permitindo a aplicação de condições controladas, desacoplamento de mecanismos e configurações que geralmente não são alcançáveis em experimentos físicos, garantindo que nenhuma outra variável indesejável esteja agindo no sistema. Neste trabalho, simulações de dinâmica molecular (MD) foram usadas para explorar sistematicamente o efeito de massa do isótopo na contribuição fonônica para o atrito, simulando diferentes condições de carga, direção de deslizamento e cobertura de superfície para superfícies planas de cristal único de diamante [111] passivadas com H. Simulações foram realizadas utilizando o potencial Adaptive Intermolecular Reactive Empirical Bond-Order (AIREBO), incluindo as interações de van der Waals. O coeficiente de atrito foi considerado independente da massa atômica do adsorbato para ambas as direções de deslizamento simuladas. Além disso, pelo menos nas condições simuladas, uma simples redução na cobertura da superfície também não afetou significativamente o coeficiente de atrito. Um aumento acentuado da força de atrito foi observado apenas quando a camada de passivação foi modificada pela introdução de defeitos altamente reativos. Por conseguinte, os resultados das simulações de dinâmica molecular dão suporte a um efeito isotópico indireto no atrito, mas apenas na medida em que os defeitos criados na camada de passivação levam à formação de superfícies altamente reativas. [resumo fornecido pelo autor]
Keywords: Dinâmica molecular; Isótopos; Atrito; Molecular dynamics; Isotopes; Friction